Higher-order symmetric duality for a class of multiobjective fractional programming problems - Ying, Gao (Journal of inequalities and applications, 2012)
In this paper, a pair of nondifferentiable multiobjective fractional programming problems is formulated. For a differentiable function, we introduce the definition of higher-order ( F , α , ρ , d )-convexity, which extends some kinds of generalized convexity, such as second order F -convexity and higher-order F -convexity. Under the higher-order ( F , α , ρ , d )-convexity assumptions, we prove the higher-order weak, higher-order strong and higher-order converse duality theorems. Mathematics Subject Classification (2010) 90C29; 90C30; 90C46.